Dreams of a final theory - Weinberg, Steven, 1933-2021. (New York : Pantheon Books, 1992)
"From one of the world's most distinguished scientists, here is the story of a great intellectual adventure of our time: the search for nature's final laws." "The success of physics in this century has been stunning, transforming our views of space and time, of reality and knowing, changing the very language we use to describe nature. At the close of the century we stand in possession of a new view of the universe, one in which the old centrality of matter is gone, and nature's symmetries lie at the core of our understanding. The driving force behind these revolutions in thought has been the search for the ultimate laws of nature - for the final answer to our questions about why nature is the way it is." "In Dreams of a Final Theory, Steven Weinberg imagines the shape of a final theory, and the effect its discovery will have on the human spirit. Along the way he gives a spirited defense of reductionism - the impulse to trace the explanations of natural phenomena to deeper and deeper levels - and examines the curious relevance of beauty in scientific theories. He gives us a compelling personal account of the search for the laws of nature as a part of the intellectual history of our times, and shares with us the glimpses that scientists have had from time to time that there is something behind the blackboard - a deeper truth foreshadowing a final theory."--BOOK JACKET.
"January 1993"--Cover.
Includes bibliographical references (p. 291-329).
Keywords: Physics; Relativity (Physics); Quantum theory